Pengaruh Pelayanan, Disiplin, Dan Lingkungan Terhadap Kepuasan Pasien Pada Puskesmas Janapria Lombok Tengah - Opil Krismantara; Nizar Hamdi; Rosyia Wardani (Lembaga Pengembangan, Penelitian dan Pengabdian Kepada Masyarakat (LP3M) Sekolah Tinggi Ilmu Ekonomi AMM (STIE AMM) Mataram, 2025)
This research aims to determine whether service, discipline and environment have a significant simultaneous influence on patient satisfaction at the Janapria Health Center in Central Lombok. So this research variable consists of three (3) independent variables, namely Service (X1), Discipline (X2), Environment (X3) and the dependent variable, namely Patient Satisfaction (Y). The population in this study were people who had used services at the Central Lombok Janapria Community Health Center, the number of which is not known with certainty. The method used in this research is non-probability sampling. “Non-probability sampling is a sampling method that does not give each element or member of the population the same opportunity to be selected as a sample. In the sample size, the researcher took the 3rd point, namely a minimum sample size of 10 times the number of variables studied. So the number of sample members is 10 x 4 = 40 respondents in this study. Data is processed using SPSS. The results of this research show that service, discipline and environment have a significant effect on patient satisfaction at the Janapria Health Center, this can be seen from the calculated f value of 73.504 which is greater than the f table value of 2.81 with a significance level of 0.000 which is smaller than 0.05.